Feasibility study: PETRONAS Aviation Sdn Bhd to enter China Aviation market / Fara Eda Katrina Ramli - Ramli, Fara Eda Katrina (Faculty of Business and Management, 2011)
PETRONAS Aviation Sdn Bhd is a Petroliam Nasional Berhad (PETRONAS) subsidiaries that formed to consolidate PETRONAS global jet fuel business. The growth of airlines passengers each year influenced the demand in jet fuel. PETRONAS Aviation Sdn Bhd presence in Hong Kong, Brunei, Sudan, Bangkok and few mores countries especially in Asia and Africa region. Besides of jet fuel business, PETRONAS Aviation Sdn Bhd also offers Technical Service Agreement (TSA) such as operations services, project consultancy services, inspection services and training service. Main objective for this paper is to study the overview of China market whether it is a significant market for PETRONAS Aviation Sdn Bhd to expand their jet fuel business. In order to do that, researcher focus on the jet fuel forecast, the economy environment in China, China regulatory practise, and lastly researcher to implement the famous Porter Five method by modified it with PETRONAS Aviation Sdn Bhd suitability.